(untitled) - Slavíková, Marie (Aura musica, 2021)
The paper informs about the author's experience with distance teaching of music subjects in the study program Teacher Training for Primary Schools. We find positive results in the teaching of theoretical and practical components of the study, but we also reflect on some negatives. We want to continue to use good experience from distance learning in full-time or part-time teaching.
Keywords: distance learning; music education; music skills; didactics of music education